2009
DOI: 10.1038/aja.2008.5
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic porcine spermatogenesis in murine subcutis: tissue grafting versus cell-injection methods

Abstract: Fragments of testis tissue from immature animals grow and develop spermatogenesis when grafted onto subcutaneous areas of immunodeficient mice. The same results are obtained when dissociated cells from immature testes of rodents are injected into the subcutis of nude mice. Those cells reconstitute seminiferous tubules and facilitate spermatogenesis. We compared these two methods, tissue grafting and cell-injection methods, in terms of the efficiency of spermatogenesis in the backs of three strains of immunodef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…We concluded that addition of Matrigel to the mixture enhances tubule formation and decreases the requirement for large numbers of donor cells, which is beneficial for future studies in animal models where the availability of donor tissue may be limited. The positive influence of Matrigel on the development of tissue from a smaller number of testicular cells is in accordance to what has been reported (Kita et al 2007, Watanabe et al 2009). Similarly, this matrix has been used to support tumor growth or maintenance of pancreatic islets in xenogenic hosts (Ruggeri et al 2002, Dufour et al 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We concluded that addition of Matrigel to the mixture enhances tubule formation and decreases the requirement for large numbers of donor cells, which is beneficial for future studies in animal models where the availability of donor tissue may be limited. The positive influence of Matrigel on the development of tissue from a smaller number of testicular cells is in accordance to what has been reported (Kita et al 2007, Watanabe et al 2009). Similarly, this matrix has been used to support tumor growth or maintenance of pancreatic islets in xenogenic hosts (Ruggeri et al 2002, Dufour et al 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The influence of number of cells grafted was determined comparing tubule formation when the same conditions were provided to different number of cells grafted; our results supported what has been previously hypothesized (Watanabe et al 2009), that the number of cells grafted are correlated with tubule formation.…”
Section: Discussionsupporting
confidence: 88%
“…As basement membrane components seem to be physiologically appropriate for the 3D culture of testicular cells, matrigel matrix provides a 3D environment for germ cell differentiation. Previous studies have indicated that spermatogenic efficiency and testis tubule formation can be improved by the addition of matrigel [ 37 39 ]. Therefore, matrigel matrix was selected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a higher severity of immunodeficiency in recipients may provide a more suitable host environment for the development of xenografts (Ito et al 2002). In a few studies, severe combined immunodeficient (SCID) mice, which lack both T and B lymphocytes, have been used successfully in testis tissue xenografting with no obvious changes in the outcomes (Rathi et al 2005(Rathi et al , 2006Geens et al 2006;Goossens et al 2008;Watanabe et al 2009).…”
Section: Introductionmentioning
confidence: 99%